2018
DOI: 10.1111/phn.12409
|View full text |Cite
|
Sign up to set email alerts
|

Community/public health nursing faculty's knowledge, skills and attitudes of the Quad Council Competencies for Public Health Nurses

Abstract: Ten recommendations are proposed for key skill sets and necessary preparation for faculty to effectively teach C/PHN in baccalaureate schools of nursing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Many nursing programs have turned to non‐traditional clinical settings as opportunities for clinical placement in traditional public health clinical sites have continued to shrink. Other authors have identified the need to provide enhanced student support and public health role modeling as well as improved faculty development opportunities in public health to ensure students have optimal clinical experiences in non‐traditional clinical settings (Joyce et al, ; Leurer et al, ; Pijl‐Zieber, Barton, Awosoga, & Konkin, ; Pijl‐Zieber & Kalischuk, ; Wade & Hayes, ). It is imperative to continue to work with our traditional clinical settings in county and governmental public health agencies to provide clinical placements to as many students as possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many nursing programs have turned to non‐traditional clinical settings as opportunities for clinical placement in traditional public health clinical sites have continued to shrink. Other authors have identified the need to provide enhanced student support and public health role modeling as well as improved faculty development opportunities in public health to ensure students have optimal clinical experiences in non‐traditional clinical settings (Joyce et al, ; Leurer et al, ; Pijl‐Zieber, Barton, Awosoga, & Konkin, ; Pijl‐Zieber & Kalischuk, ; Wade & Hayes, ). It is imperative to continue to work with our traditional clinical settings in county and governmental public health agencies to provide clinical placements to as many students as possible.…”
Section: Discussionmentioning
confidence: 99%
“…There has been widespread use of Quad Council of Public Health Nursing Organizations Core Competencies for Public Health Nurses (Core Competencies) in academia (Brown, ; Campbell, ; Issel, Baldwin, Lyons, & Madamala, ; Jakeway, Cantrell, Cason, & Talley, ; Joyce et al, ; Oppewal, Lamanna, & Glenn, ; Siemon, Gallegos & Gehrke, ) and practice (Issel et al, ; Oppewal et al, ; Zahner & Henriques, ). Additionally, there have been increased calls to use public health competencies when developing and revising nursing curricula to ensure students have the knowledge, skills, and attitudes needed to provide population focused interventions (Brown, ; Carter, Kaiser, O;Hare, & Callister, ; Keller, Schaffer, Schoon, Brueshoff, & Jost, ; Siemon et al, ; Swider et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Problematic areas of the CET included duplication in content, appropriateness of specific competencies, and subsequent length of the CET. Results of this QI led to the following actions and outcomes: Planned and implemented presentations to share findings and advocate for competency‐based education with nursing faculty organizations, curriculum committees and within schools of nursing. Utilized competencies to structure course, organize didactic content, simulation and practicum content, and support curricula change. Presented three national webinars to nurses to review competencies and clinical application. Repeated orientation/training of competencies each semester with faculty and community partners. Developed a coalition entitled “Partners in Population Health” at one university. Developed and implemented two funded research projects to validate the utilization of the competencies with C/PHN faculty (Joyce, Harmon, et al, ) and public health nurses working in government agencies. Conducted a content analysis crosswalk (Joyce, Brown‐Schott, et al, ) for global health (Wilson et al, ) and interprofessional global health competencies (Jogerst et al, ). Presented findings to the Quad Council Coalition and discussed concerns related to redundancy and appropriateness of competencies for baccalaureate nursing education. Invited appointments of two members from the multisite team to a Quad Council task force to review and revise the QCC‐PHN . …”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Education based on competency is an important goal (Joyce, Harmon, et al, ). However, nursing faculties throughout the United States struggle to determine which competencies are most critical to educate baccalaureate students (Callen et al, ; Tilley, ).…”
Section: Introductionmentioning
confidence: 99%